(untitled) - Pearse, Andrew (Oxford, 1980)
Seeds of Plenty, Seeds of Want: Social and Economic Implications of the Green Revolution. This book introduce the new technology and the peasants, political motors of technological innovation. Communal tenure structures and an African experiment, the dynamics of bi-modal structures...
Keywords: Cách mạng xanh,Green revolution; Các nước đang phát triển,Developing countries